2007
DOI: 10.1353/dem.2007.0033
|View full text |Cite|
|
Sign up to set email alerts
|

The association of childhood socioeconomic conditions with healthy longevity at the oldest-old ages in China

Abstract: Based on unique data from the largest-ever sample of the Chinese oldest-old aged 80 and older, our multivariate logistic regression analyses show that either receiving adequate medical service during sickness in childhood or never/rarely suffering from serious illness during childhood significantly reduces the risk of being ADL (activities of daily living) impaired, being cognitively impaired, and self-reporting poor health by 18%–33% at the oldest-old ages. Estimates of effects for five other indicators of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
136
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 56 publications
8
136
0
1
Order By: Relevance
“…Another poslimited educational facilities. Although some young elders attended school during adulthood in the national illiteracy eradication movement, 55 prevalence of literacy is much lower among women (34%) than among men (75%). Further, a majority of Chinese elders are illiterate, and some literate elders might have been politically persecuted during the Cultural Revolution.…”
Section: Discussionmentioning
confidence: 99%
“…Another poslimited educational facilities. Although some young elders attended school during adulthood in the national illiteracy eradication movement, 55 prevalence of literacy is much lower among women (34%) than among men (75%). Further, a majority of Chinese elders are illiterate, and some literate elders might have been politically persecuted during the Cultural Revolution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in western countries have found that education has a strong effect on seniors' health, both influencing the individual's ability to access health care and as a proxy for SES status over the life course (Dalstra et al 2006;Grundy and Holt 2001). Education may play a different role for Chinese elderly, many of whom have had limited access to education over their life course (Zeng et al 2007). For them, the influence of family care on SRH may be more meaningful than individual education.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al (2007) found that receiving adequate medical services in childhood could reduce the risk of being ADL disabled among Chinese oldest-old men and women by 18 % and 22 %, respectively. Luo and Waite (2005) similarly found that U.S. adults aged 50 and older who had relatively disadvantaged childhoods or adulthood socioeconomic conditions had greater functional limitations than their counterparts who grew up in more well-off families; however, the negative impact of poor childhood conditions can be ameliorated by better SES in adulthood.…”
Section: (R)esourcesmentioning
confidence: 99%
“…Research on associations between SES at different life stages and disability at late ages has flourished in last two decades Most studies have demonstrated that a strong association between early life or mid-life stage and physical functioning at later ages in various countries with different levels of income (Freedman et al 2013;McEniry 2013;Schoeni et al 2008;Wen and Gu 2011;Zeng et al 2007). Zeng et al (2007) found that receiving adequate medical services in childhood could reduce the risk of being ADL disabled among Chinese oldest-old men and women by 18 % and 22 %, respectively.…”
Section: (R)esourcesmentioning
confidence: 99%